Exploring Opportunities for 3d Printing Construction in Emerging Contexts: Through the Design of a Vocational Training College in Philippi - Snyman, Marie (School of Architecture, Planning and Geomatics, 2023)
The dissertation aims to emphasize the connection between methods and materials of construction and architectural design. How construction leads to design and design can lead to construction. Secondly, the work aims to highlight how architects can boost innovation in the construction industry through design. Speculative designs of local projects that showcase the potential of 4th Industrial revolution (IR) technologies can accelerate the local development and adoption of modern methods. The new manufacturing technologies promise great potential in the South African context as they are more sustainable and effective. The project focuses on 3D printing construction and investigates the potential and limitations of the technology in the local context. It also looks at how the capabilities and restrictions of the technology influence the language of the architecture it produces. The research is done within the context of a struggling economy in the developing city node of Philippi, Cape Town. The value and implications of introducing a revolutionary technology, such as 3D Printing construction in a place like Philippi are investigated through the design of a Technical and Vocational Education and Training (TVET) college. The college's main objective is to educate and promote the use of 3D printing manufacturing. The school building, workshops and public facilities are not only built using 3D printing construction but also train locals in the craft to give them useful and modern skills that will soon be in high demand as the technology matures to become a mainstream fabrication method internationally and in South Africa.